Encyclopedia of Environmetrics 2012
DOI: 10.1002/9780470057339.vac003.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Capture–Recapture Sampling Designs

Abstract: Good study design is necessary to obtain unbiased and efficient results from capture–recapture (CR) studies. We describe the considerations necessary for successful completion of CR studies. Rather than focusing on analytical issues, we discuss the stochastic processes that give rise to the data derived from such studies. We focus on the attributes of studies necessary to ensure that the assumptions of analyses associated with CR studies are met. We hope to expose investigators to data collection issues associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…The extent to which this assumption can be acceptably violated remains unclear, although it has been reported that <1% of violated occasions would create a small bias (O'Connell-Goode, Lowe & Clark 2014). This issue was dealt with in our study by pooling the coastal sites (Scenario 2) (Schwarz 2002), while also ensuring that all states were sampled equally (Crespin et al 2008). However, this procedure may lead to more heterogeneity in capture probabilities and bias survival rates and abundance estimates (Pollock et al 1990).…”
Section: I M I T a T I O N Smentioning
confidence: 99%
“…The extent to which this assumption can be acceptably violated remains unclear, although it has been reported that <1% of violated occasions would create a small bias (O'Connell-Goode, Lowe & Clark 2014). This issue was dealt with in our study by pooling the coastal sites (Scenario 2) (Schwarz 2002), while also ensuring that all states were sampled equally (Crespin et al 2008). However, this procedure may lead to more heterogeneity in capture probabilities and bias survival rates and abundance estimates (Pollock et al 1990).…”
Section: I M I T a T I O N Smentioning
confidence: 99%